Modelling the kinetics of peroxidase inactivation, colour and texture changes of pumpkin (Cucurbita maxima L.) during blanching - Gonçalves, E. M. (2010)
The effects of blanching treatment on peroxidase inactivation, colour and texture of pumpkin (Cucurbita maxima L.) were studied in the temperature range of 75–95 C. Peroxidase inactivation followed a first-order Arrhenius model, where the activation energy and rate of the reaction at a reference temperature of 85 C were 86.20 ± 5.57 kJ mol 1 and 0.27 ± 0.01 min 1, respectively. During blanching, pumpkin became darker and softer with processing time. The degradation of colour (evaluated throughout CIE L*a*b* colour system, with chroma index and total colour difference) and texture parameters (firmness and energy) showed a fractional conversion model kinetics, being the temperature effect on kinetic parameters well described by the Arrhenius law. The results of this work are a good tool to further optimise pumpkin blanching conditions.